Độ bền dai tách lớp và tính chất cơ học của vật liệu polyme compozit trên cơ sở nhựa epoxy epikote 828/OELO gia cường sợi cacbon, đóng rắn bằng xyanetyldietylentriamin - Trung, Đặng Hữu; Duy Linh, Nguyễn Phạm; Diệu, Trần Vĩnh; Yến Oanh, Đoàn Thị (Vietnam Journal of Chemistry, 2016)
Carbon fabric/epoxy (CF/EP) composite toughened by OELO was prepared to improve fracture toughness of the composite. The obtained testing results showed that the Izod impact strength of carbon fabric/epoxy composites significantly increased by 31.4 % from 37.2 KJ/m2 to 48.9 KJ/m2 just by adding 6 phr (part per hundred of resin) OELO was dispersed in the epoxy matrix. Both mode-I interlaminar fracture toughness of carbon fabric/epoxy (OELO/EP) composites at crack initiation and propagation also improved by 37.2 % and 17.7 %, respectively by content of 6 phr OELO in compositions. Damaged surfaces of fractured samples were investigated using scanning electron microscopy (SEM) techniques. Results obtained from dynamic mechanical thermal analysis (DMTA) showed that the glass transition temperatures of the epoxy resin matrix were slightly reduced on the addition of 6phr OELO. Keywords. Epoxy resin, fracture toughness, epoxidized linseed oil oligomer, composite materials